2009 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2009
DOI: 10.1109/iembs.2009.5334726
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a single accelerometer based biofeedback system for real-time correction of neck posture in computer users

Abstract: The worldwide adoption of computers is closely linked to increased prevalence in neck and shoulder pain. Many ergonomic interventions are available; however, the lifetime prevalence of neck pain is still estimated as high as 80%. This paper introduces a biofeedback system using a novel single accelerometer placement. This system allows the user to react and correct for movement into a position of bad posture. The addition of visual information provides artificial proprioceptive information on the cranial-verte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 17 publications
(16 reference statements)
1
43
0
1
Order By: Relevance
“…Breen et al [70] used a biofeedback system which used a single accelerometer to correct neck posture in computer users. Crowell and colleagues [71] found that individuals can use real-time feedback of tibial acceleration from an accelerometer to reduce loading on their lower extremities while running and they can maintain the reductions for at least ten minutes after the feedback is removed.…”
Section: Biomechanical Biofeedbackmentioning
confidence: 99%
“…Breen et al [70] used a biofeedback system which used a single accelerometer to correct neck posture in computer users. Crowell and colleagues [71] found that individuals can use real-time feedback of tibial acceleration from an accelerometer to reduce loading on their lower extremities while running and they can maintain the reductions for at least ten minutes after the feedback is removed.…”
Section: Biomechanical Biofeedbackmentioning
confidence: 99%
“…In a study comfortable head and neck posture at computer workstations, Ankrum and Nemeth [43] suggested that the mean observed head tilt (Ear-Eye Line 7.7° above horizontal) and head/neck posture of 43.7° in C7-tragus against vertical are more flexed. Breen et al [11] measure head and neck angle by placing an accelerometer device at the C7 vertebrae directly, as measuring the cranial-vertebral angle.…”
Section: Biofeedbackmentioning
confidence: 99%
“…The investigation results on the effects of biofeedback on the sitting posture of a 14-year-old girl with cerebral palsy indicate a significant improvement in posture [10]. Breen et al [11] develop a biofeedback system for real-time correction of neck posture in computer users. All the six subjects have a significant decrease in the percentage of time spent in bad posture when using biofeedback.…”
Section: Introductionmentioning
confidence: 99%
“…Research has also shown that sensor based feedback from an accelerometer can be given to subjects in order to modify their movement or behaviour. Reference [8] examined the use of a biofeedback system which used a single accelerometer to correct neck posture in computer users. Reference [9] found that real-time visual feedback from an accelerometer could be used to achieve immediate reductions in tibial acceleration and vertical-force loading rates and thus reducing that individual's risk of a stress fracture.…”
Section: Introductionmentioning
confidence: 99%